Câncer de mama, religiosidade e espiritualidade - Raissa Cristina Abreu Couto (2015)
The purpose of this work is to understand possible associations between religious involvement and coping for patients diagnosed with breast cancer. It was conducted 19 individuals in depth interviews with patients undergoing chemotherapy for breast cancer, and applied a survey questionnaire to all of them. The data analysis was made from the content analysis (CA). It was observed that the women interviewed pointed out that not only your healing, but also the possibility of passing the illness experience, served to strengthen their religious convictions, and pointed out that their faith played a key role in their healing and in the fact go through process positively disease. Thus, they ended up creating a cycle in which both religious beliefs as their health are seen as strengthened.